Design, build, test and flight of the world's fastest electric aircraft - Timothy Bingham; Mathew Moore; Taylor DeCaux; Marco Pacino (IET Electrical Systems in Transportation)
Abstract Power to mass ratio is one of the key characteristics of most high‐performance vehicles, a record‐breaking ACCEL race aircraft is no different. Project ACCEL pushed the limits of energy management, thermal management, and mass saving, while maintaining measured safety for the pilot and crew to ultimately achieve world record‐breaking flights. The numerous engineering challenges involved in designing and developing the world's fastest electric aircraft have been solved by a relatively small team in a limited timeframe. The blank sheet design of the ESS and powertrain allowed for an appropriately optimised solution, swiftly moving into physical testing allowed for rapid development of the system and opportunities to iterate. In the closing stages of the project, building, assembling, and ground testing the aircraft under one roof allowed for an effective cohesive and exciting crescendo before flight operation of the aircraft at MoD Boscombe Down.